Optimizing Economic Complexity - Stojkoski, Viktor; César A. Hidalgo (My University, 2025)
Efforts to apply economic complexity to identify diversification opportunities often rely on diagrams comparing the relatedness and complexity or products, technologies, or industries. Yer, the use of these diagrams is not based on empirical or theoretidal evidence supporting some notion of optimality. Here, we introduce an optimization-based framework that identifies diversification opportunities by minimizing a cost function capturing the constraints imposed by an economy's pattern of specialization. We show that the resulting portfolios often differ from those implied by relatedness-complexity diagrams, providing a target-oriented optimization layer to the economic complexity toolkit.
Keywords: econ.GN; econ.GN